230k views
1 vote
1st. (2 root 2 + root 3 ) ( 2 root 3 - root 2)

2nd.(root 5 + 2 root 10) (3 root 5 + root 10)
3rd.(4 root 6 - 3 root 3) (2 root 3 - 5)
4rd. (6 root 3 - 5 root 2 ) (2 root 2 - root 3)
5th. (root 10 - 3 ) ( 4 - 3 root 10)

1 Answer

5 votes

Answer:

1st: 3*root6 + 5

2nd: 35*root2 + 115

3rd: 24*root2 - 20*root6 + 15*root3 - 18

4th: 17*root6 - 38

5th: 13*root10 - 42

Explanation:

To simplify these expressions we need to use the distributive property:

(a + b) * (c + d) = ac + ad + bc + bd

So simplifying each expression, we have:

1st.

(2 root 2 + root 3 ) ( 2 root 3 - root 2)

= 4*root6 - 2*2 + 2*3 - root6

= 3*root6 - 4 + 9

= 3*root6 + 5

2nd.

(root 5 + 2 root 10) (3 root 5 + root 10)

= 3 * 5 + root50 + 6*root50 + 2*10

= 15 + 5*root2 + 30*root2 + 100

= 35*root2 + 115

3rd.

(4 root 6 - 3 root 3) (2 root 3 - 5)

= 8*root18 - 20*root6 - 6*3 + 15root3

= 24*root2 - 20*root6 + 15*root3 - 18

4rd.

(6 root 3 - 5 root 2 ) (2 root 2 - root 3)

= 12*root6 - 6*3 - 10*2 + 5*root6

= 17*root6 - 18 - 20

= 17*root6 - 38

5th.

(root 10 - 3 ) ( 4 - 3 root 10)

= 4*root10 - 3*10 - 12 + 9*root10

= 13*root10 - 30 - 12

= 13*root10 - 42

User Xiaoxia Lin
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.